The Effect of the Herringbone Technique on Reading Comprehension - Rengganis Siwi Amumpuni (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The purpose of this research is to know the effect of the Herringbone technique on students' reading comprehension. A quasi-experimental was used in this research and the sample was 20 students of Guidance and conselling department . Test was used in this research to collect the data and the data was analyzed by paired sample T-test by using SPSS. The result of this research, there was a significant effect of the herringbone to the students 'reading comprehension. It can be seen from the value of the t-test that the score was higher than t- table (11.212 > 2.086). Therefore, it can be stated that the there is a significant effect of Heringbone technique on students’ reading comprehension.